Residential Investment and Recession Predictability - Knut Are Aastveit; AndreḰ. Anundsen; Eyo I. Herstad (Norges Bank, 2017)
We assess the importance of residential investment in predicting economic recessions for an unbalanced panel of 12 OECD countries over the period 1960Q1-2014Q4. Our approach is to estimate various probit models with different leading indicators and evaluate their relative prediction accuracy using the receiver operating characteristic curve. We document that residential investment contains information useful in predicting recessions both in-sample and out-of-sample. This result is robust to adding typical leading indicators, such as the term spread, stock prices, consumer condence surveys and oil prices. It is shown that residential investment is particularly useful in predicting recessions for countries with high homeownership rates. Finally, in a separate exercise for the US economy, we show that the predictive ability of residential investment is robust to employing real-time data.
hdl:11250/2495539
Keywords: C33; C53; E32; E37; 330; recession predictability; leading indicators; real-time data; housing